2013
DOI: 10.1037/a0030549
|View full text |Cite
|
Sign up to set email alerts
|

Health service utilization before and after evidence-based treatment for PTSD.

Abstract: Posttraumatic stress disorder (PTSD) is associated with functional impairment, co-occurring diagnoses, and increased health care utilization. Associated high demand for health care services is an important contributor to the large public-health cost of PTSD. Treatments incorporating exposure therapy are efficacious in ameliorating or eliminating PTSD symptoms. Accordingly, the Veterans Health Administration has made significant investments toward nationwide dissemination of a manualized exposure therapy protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 49 publications
(53 reference statements)
3
68
2
Order By: Relevance
“…23,25,26 Treatment, specifically evidence-based treatments for PTSD, can reduce the suffering and interference related to trauma symptoms 39 and also decrease mental health service utilization following completion of treatment. 40 The present study has a number of limitations that should be noted. The sample was a predominantly male and Caucasian sample of veterans, which limits generalizability to civilian populations as well as to female veterans.…”
Section: Resultsmentioning
confidence: 86%
“…23,25,26 Treatment, specifically evidence-based treatments for PTSD, can reduce the suffering and interference related to trauma symptoms 39 and also decrease mental health service utilization following completion of treatment. 40 The present study has a number of limitations that should be noted. The sample was a predominantly male and Caucasian sample of veterans, which limits generalizability to civilian populations as well as to female veterans.…”
Section: Resultsmentioning
confidence: 86%
“…A single-site study of veterans in Charleston, South Carolina, demonstrated that evidence-based treatment for PTSD was associated with large reductions in symptoms and that diagnostic remission was associated with substantial reductions in mental health service utilization and health care costs, particularly for veterans who completed treatment (Tuerk et al, 2013). Similarly, researchers at the Minneapolis VA noted a decrease in individual and group therapy after veterans had received treatment for PTSD, amounting to a 39.4% decrease in cost associated with mental health care (Meyers et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, the authors recommended that Veterans should be empowered to seek evidence-based treatments and the Department of Defense and Veterans Affairs Healthcare System should attempt to increase their capacity to deliver these treatments. Tuerk et al (2013) examined health-service utilization among Veterans who received Prolonged Exposure within a VA PTSD specialty clinic and found that, contrary to their hypotheses, Veterans who dropped out of PE continued to use mental health services at a significantly higher rate than those Veterans who completed PE. This finding underscores the economic cost of Veterans not receiving EBPs for PTSD, as the authors estimated the clinic saved $11,644 due to offering PE to the Veterans enrolled in the study.…”
mentioning
confidence: 81%
“…Thus, the people who opted to receive supportive counseling or psychoeducation over a trauma-focused treatment were significantly less likely to achieve PTSD symptom remission. Although a VA PTSD Clinical Team (PCT) may want to provide ongoing support/coping for EBP nonresponders or dropouts, the clinic and Veterans will likely benefit from allocating most staff resources to providing EBPs like Prolonged Exposure because they will increase capacity which will result in more Veterans being treated (Tuerk et al, 2013). It would seem that the more clients seen would offer more opportunities to provide patient-centered care.…”
Section: What Is Patient-centered Care For Ptsd?mentioning
confidence: 99%